Change and Development of the Second House in Istanbul Coastal Areas - Yazgan, Ayfer (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2018)
It is known that the second housing is primarily seen in developed countries due to the increase in purchasing power and in free time. Within the process, changes in lifestyles, high demand for leisure time use and recreational activity; have been seen as the most important reasons for the conceptual development of the secondary housing term. The second housing, which has became an integral part of the urban life, reshapes the economic structure by differentiating the socio-cultural structure of the space and determines the growth direction of the settlement areas. For these reasons, the second housing emerges as one of the important dynamics in the formation and growth of the urban space. Sprawling urban development of Istanbul towards the second housing areas is a phenomenon that refers to extent urbanization. Especially after 1980, it is seen that the increase in the population and the increase in the construction has been effective in transforming the secondary residential areas into the urban residential areas. The main purpose of the study is to question the relations between social structures and spatial characters (space quality, accessibility, effect on the natural structure, usage-consumption balance) of the second housing areas choosing place on the shores of Istanbul. While explaining the criterias for site selection of secondary housing areas, the study reveals how the defined relationships have changed in the historical process and how the growth direction of the city has influenced. Within this scope, the objective is to figure out the user profile and spatial development of the second houses in the different coastal areas of Istanbul. Using the data obtained from the questionnaire studies, the different social, economic and spatial structures of the second housing estates clustered in different subregions were discussed comparatively.
Keywords: Physical and social transformation; mobility; second house; spatial analysis; Architecture